The Effectiveness of Educational Program Based On BASNEF Model on the Urban Taxi Drivers' Healthy Lifestyle - KheirMohammad Jadgal; Hadi Alizade Seiouki; Behrouz Lotfi Mayen Boulagh; Iraj Zareban (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: More than one-third of deaths is caused by wrong social and personal lifestyle in the world. The present study aimed to find out the effect of education program based on the BASNEF model on healthy lifestyle of Konarak taxi drivers. Materials and methods: Framework of this study was a quasi-experimental study. Data was collected by research-made questionnaire based on BASNEF Model structures. 160 taxi drivers of Konarak city were selected as samples by Multi-stage random sampling method and divided into case and control groups. Then educational sessions were performed in the case groups. The training materials used in educational Sessions were pamphlets. The intervention included 2 training sessions for 1 month. Both groups were followed for two months after the intervention to perform the post-test. The data were analyzed using SPSS 16 and descriptive and analytical tests (t-test, Pearson, and Chi Square) (p < 0.05). Results: The mean score of knowledge, attitude, behavior and Enabling Factors increased significantly after intervention (p < 0.001). Physicians and health personnel were the most frequent of subjective norms. Conclusion: Implementing educational intervention programs can increase the level of knowledge, attitude, and behavior of drivers regarding healthy lifestyle. Paper Type: Research Article.